2022
DOI: 10.1016/j.ijso.2021.100436
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, attitude, practice and associated factors of venous thromboembolism prophylaxis among health professionals. A cross sectional study

Abstract: Introduction: Venous thromboembolism (VTE) is a leading cause of postoperative morbidity. In hospitalized patients, it is a common and potentially fatal complication. Knowledge, positive attitude, and effective practice on VTE prophylaxis are vital for the proper management of patients. Inadequate knowledge and poor practice of health professionals towards VTE prophylaxis increased patients’ complications. Objective: To assess knowledge, Att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The fear of patient complications, skin breakdown, and bleeding deters nurses from applying mechanical prophylaxis devices to their patients. 24 , 44 Existing studies have shown that nurses perceived VTE mechanical prophylaxis as a risk outweighing benefits and stated that it was not relevant to their setup. 45 Such perception reflects an erroneous belief related to the benefits of VTE mechanical prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…The fear of patient complications, skin breakdown, and bleeding deters nurses from applying mechanical prophylaxis devices to their patients. 24 , 44 Existing studies have shown that nurses perceived VTE mechanical prophylaxis as a risk outweighing benefits and stated that it was not relevant to their setup. 45 Such perception reflects an erroneous belief related to the benefits of VTE mechanical prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…The survey allows a better understanding of the current status of a population’s Knowledge (K), Attitudes (A), and Practices (P) towards a specific matter, such as PTs, as well as potential issues within the current state and barriers to safe clinical application. Previous KAP studies undertaken among orthopedic surgeons helped to gain a better insight and plan additional educational interventions regarding surgical antibiotic prophylaxis [ 13 ], pain management [ 14 ], and venous thromboembolism [ 15 , 16 ]. A few studies assessing tourniquet usage reported adequate practice among medical personnel [ 17 ] and low knowledge among patients [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the overall attitude towards VTE prophylaxis was positive, nurses exhibited poor knowledge, which was attributed to a lack of training programs. In a study conducted by Kiflie et al (2022), it was discovered that at least 65% of nurses possessed a good understanding of VTE prophylaxis. Nurses play a critical role in preventing VTE, and inadequate knowledge is perceived as the primary obstacle to conducting VTE risk assessments (Lee et al, 2014).…”
Section: Introductionmentioning
confidence: 99%